TECHNIQUES OF REMOTE SENSING APPLIED TO MAPPING OF LAND USE AND COVER ON THE ARROIO CAPÃO, SÃO GABRIEL – RS - Fantinel, Roberta; Palmeira, Aline Negreira; Santos, Maria Aparecida Possati dos; Benedetti, Ana Carolina Paim (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704362 This paper presents the actions developed in the remote sensing with objetive of analyzehistorical and current data regarding the use and occupancy of the soil located in the ArroioCapão, located in River Cacequi in São Gabriel in Rio Grande do Sul. For this, we used images ofthe sensor Thematic Mapper (TM) onboard the Landsat 5 satellite, of different dates, one of theyear 1985 and another in 2010. Classification was performed by supervised type MaximumVerossimilhana. The classes considered were water, field, forest and bare soil. The analysisshowed the temporal dynamics of the classifications of land cover classes allowing to ascertainthat a large part of the class field in 1985 was converted to bare soil class in 2010. In this sense,the environmental changes observed show that incorrect practices of soil management areresponsible for transforming the landscape of the study site.